Correlates of life-history variation in the livebearing fish Poecilia vivipara (Cyprinodontiformes: Poeciliidae) inhabiting an environmental gradient - Rius, Bianca F. [UNESP]; Petry, Ana Cristina; Langerhans, R. Brian; Figueiredo-Barros, Marcos P.; Bozelli, Reinaldo L.; Honda, Laura K. [UNESP]; Nova, Clarice C.; Araújo, Márcio S. [UNESP] (Oxford University Press (OUP), 2019)
Understanding whether and how different habitat features affect patterns of life-history variation is an intriguing aim in evolutionary ecology. We tested how a suite of biotic and abiotic factors simultaneously affect life-history patterns in six populations of the livebearing fish Poecilia vivipara inhabiting coastal lagoons in southeastern Brazil, varying greatly in salinity and fish communities. We sampled potential competitors (cyprinodontiform fishes) and piscivores, and we measured nine limnological variables in the wet and dry seasons during 2 years. We found that size at maturity and offspring size were strongly and negatively influenced by the abundance of piscivores, and that reproductive allocation was strongly and positively influenced by variations in resource abundance and temperature among seasons. Effects of salinity on size at maturity, female reproductive investment and offspring size were indirect, via piscivore abundance, highlighting the potential for indirect effects that can be detected only by analysing multiple habitat features simultaneously. This suggests caution in interpreting associations between life histories and salinity in wild populations. Observed patterns generally matched theoretical predictions and prior empirical work, but some predictions were not met. Our results suggest that life histories result from a partly predictable complex combination of direct and indirect effects of habitat features, which can sometimes act antagonistically.
Keywords: body size; coastal lagoons; fecundity; gonadosomatic index; livebearing fishes; offspring size; reproductive investment; Restinga de Jurubatiba; salinity gradient; seasonality